(untitled) (Research, Society and Development, 2025)
Nile tilapia faces challenges due to high costs and environmental impacts, including eutrophication and microbial resistance caused by excessive chemical use. Sustainable alternatives, such as probiotics and organic fertilisers, still lack comprehensive studies. This study evaluated the combined effects of the probiotic DB AQUA® with organic fertilisers (bovine, swine, and sheep) on the zootechnical performance and health of fingerlings. A total of 640 fish were tested in a recirculation system, divided into four treatments: isolated fertiliser (control) or probiotic combined with bovine, swine, or sheep fertiliser. Zootechnical parameters, hepatosomatic (HSI) and viscerosomatic (VSI) indices were analysed. The sheep fertiliser performed notably, reducing feed conversion by 60% and increasing biomass gain by 170.5 g, while also elevating HSI—indicating higher metabolic activity—and promoting 56% longer intestines, suggesting improved nutrient absorption. Survival rates did not differ between treatments, likely due to environmental factors. Bovine and swine fertilisers had limited effects, with swine presenting risks of accelerated ammonia release and pathogen contamination. In summary, the combination of DB AQUA® probiotic with sheep fertiliser significantly enhanced zootechnical performance, though its efficacy depends on water quality and management. Further studies are recommended to elucidate microbial mechanisms and economic viability on a large scale.